Employee Self Development and Work Performance in Organizational Context: Perkembangan Diri Karyawan dan Kinerja Kerja dalam Konteks Organisasi - Bima Rohmatan Aminin; Dewi Andriani; Vera Firdaus; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Employee performance remains a central concern in organizational management. Specific Background Self-development is increasingly recognized as a key factor in shaping employee work outcomes. Knowledge Gap Empirical studies examining self-development and employee performance still show varied findings across organizational settings. Aims This study aims to examine the relationship between self-development and employee performance within the selected organizational context. Results Quantitative analysis indicates that self-development demonstrates a significant association with employee performance. Novelty This study provides contextual evidence of self-development within a specific organizational setting. Implications The findings offer practical insights for organizations in supporting employee development as part of performance management strategies. Keywords: Self-Development, Employee Performance, Work Motivation, Organizational Commitment, Human Resource Management Key Findings Highlights: Employee self-development shows measurable association with work outcomes. Motivation and commitment align with performance patterns observed in the organization. Development-oriented practices support sustainable employee performance.